Characteristics of radiographic images acquired with CdTe, CCD and CMOS detectors in skull radiography - Queiroz, Polyane Mazucatto; Santaella, Gustavo Machado; Pereira de Castro Lopes, Sergio Lucio [UNESP]; Haiter-Neto, Francisco; Freitas, Deborah Queiroz (Korean Acad Oral & Maxillofacial Radiology, 2020)
Purpose: The purpose of this study was to evaluate the image quality, diagnostic efficacy, and radiation dose associated with the use of a cadmium telluride (CdTe) detector, compared to charge-coupled device (CCD) and complementary metal oxide semiconductor (CMOS) detectors. Materials and Methods: Lateral cephalographs of a phantom (type 1) composed of synthetic polymer filled with water and another phantom (type 2) composed of human skull macerated with polymer coating were obtained with CdTe, CCD, and CMOS detectors. Dosimeters placed on the type 2 phantom were used to measure radiation. Noise levels from each image were also measured. McNamara cephalometric analysis was conducted, the dentoskeletal configurations were assessed, and a subjective evaluation of image quality was conducted. Parametric data were compared via 1-way analysis of variance with the Tukey post-hoc test, with a significance level of 5%. Subjective image quality and dentoskeletal configuration were described qualitatively. Results: A statistically significant difference was found among the images obtained with the 3 detectors (P<0.05), with the lowest noise level observed among the images obtained with the CdTe detector and a higher subjective preference demonstrated for those images. For the cephalometric analyses, no significant difference (P>0.05) was observed, and perfect agreement was seen with regard to the classifications obtained from the images acquired using the 3 detectors. The radiation dose associated with the CMOS detector was higher than the doses associated with the CCD (P < 0.05) and CdTe detectors (P < 0.05). Conclusion: Considering the evaluated parameters, the CdTe detector is recommended for use in clinical practice.
Keywords: Noise; Diagnosis; Cephalometry